Positive allosteric regulation of PAC1-R up-regulates<?A3B2 ACK?>PAC1-R and its specific ligand PACAP - Fan Guangchun; Tao Zhengxin; Chen Shang; Zhang Huahua; Yu Rongjie (Acta Biochimica et Biophysica Sinica)
PAC1-R is a recognized preferential receptor for the neuropeptide of pituitary adenylate cyclase-activating polypeptide (PACAP), which mediates neuroprotective and nerve regenerative activities of PACAP. In this study, we found that in both PAC1R-CHO cells with high expression of PAC1R-eGFP and retinal ganglion cells (RGC-5) with the natural expression of PAC1-R, oligo-peptide PACAP(28-38) and the positively charged arginine-rich penetrating peptide TAT, as positive allosteric modulators of PAC1-R, significantly trigger the nuclear translocation of PAC1-R. The chromatin immunoprecipitation (ChIP)-PCR results show that the nuclear translocated PAC1-R binds with the promoter regions of PAC1-R and its specific ligand PACAP. The up-regulated promoter activities of PAC1-R and PACAP induced by PACAP(28-38) or TAT are positively correlative with the increase of the expression levels of PAC1-R and PACAP. Moreover, the nuclear translocation of PAC1-R induced by PACAP(28-38) or TAT is significantly inhibited by the mutation of PAC1-R on Cys25 and the palmitoylation inhibitor 2-bromopalmitate. Meanwhile, the increase in both PAC1-R and PACAP levels and the neuroprotective activities of PACAP(28-38) and TAT in MPP-induced cell model of Parkinson<?A3B2 tf="TT5843c571"?>’s disease are synchronously inhibited by 2-bromopalmitate, which are positively correlated with the nuclear translocation of PAC1-R induced by PACAP(28-38) or TAT. Bioinformatics analysis and motif enrichment analysis following ChIP-sequencing show that the transcription factors including SP1, Zic2, GATA1, REST and YY1 may be recruited by nuclear PAC1-R and involved in regulating the promoter activities of PAC1-R and PACAP. ChIP-sequencing and related bioinformatics analysis show that the downstream target genes regulated by the nuclear PAC1-R are mostly involved in the process of cellular stress and related to neuroprotection, neuronal genesis and development.